Fostering excellent research by the Austrian Micro Data Center (AMDC) - Regina Fuchs; Tobias Göllner; Simon Hartmann; Tobias Thomas (Journal of Economics and Statistics, 2024)
Access to high quality microdata is a precondition for the empirical investigation of many interrelationships in the economic and social sciences. Therefore, well-functioning research data infrastructure is a cornerstone of a successful science location. While other countries in Europe, such as Denmark and the Netherlands, have had microdata centres at their respective National Statistical Offices for quite some time, microdata access for research purposes in Austria was very limited for a long time. Established in 2022, the Austrian Micro Data Center (AMDC) at Statistics Austria enables researchers of accredited research institutions to work with pseudonymized microdata on individuals and firms. The available microdata includes not just microdata of Statistics Austria but also registry data of the Austrian federal government. The main novelty is that microdata can be linked deterministically to each other via unique pseudonymized identifiers among data sets of Statistics Austria, administrative registers, and also to microdata brought in by the researchers themselves. The AMDC is operated by Statistics Austria and its services are open to research institutions worldwide.
Keywords: C0; D0; 330; Austrian Micro Data Center (AMDC); data science; official statistics; register-based research; research data infrastructure; Statistics Austria